(3EOGQI GdJCejf h GdeNGWQ (B/s - (3ajGV, YQaGJ GHQGgjes ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2011)
(3CfhGY GdJCejf , Gdgjcd GdJfXjej dTQcGJ GdJCejf h gjcd GdfXGe GdeMGSHj aj gPg GdTQcGJ , SLdGJ TQcGJ GdJCejf h SLd GdJYOjdGJ h GdGdZGAGJ , YedjGJ bSe GdJCejf Ydi GdMjGI I Jchjf GdGehGd h YedjGJ EYGOI GdJGejf , GdMSGHGJ GdNJGejI h GdejRGfjI aj TQcGJ GdJGejf , ebOeI aj GdJQhjL GdJLGQj , CSGSjGJ aj GOGQI GdeUGQa (B.s
Keywords: (3GdCNWGQs; (3GdCNWGQ `` GOGQIs; (3GdEOGQIs; (3GdJCejf ` EOGQIs; (3GdJCejf (B- (3GdHfhcs